The Impact of Covid-19 Pandemic on Mental Workload and Fatigue of Students during Online and Offline Practicum - Ramadhani Dinda Safitri; Muslimah Etika; Bagaskara Wildan Bramantya; Fitriadi Ratnanto; Sakti Arga Seta Asmara (SHS Web of Conferences, 2024)
Learning activities underwent policy changes during the Covid-19 pandemic were carried out online and offline. During the Covid-19 pandemic, there were many ways that universities did to keep learning going, such as implementing online learning and online learning. Practical learning experiences changes in the teaching and learning process system due to university policies. This study aims to measure the level of mental workload and the level of student fatigue during online and offline practicums and to determine the relationship between mental workload and fatigue level. The methods used in this research are the National Aeronautics and Space Administration Task Load Index (NASA-TLX) and Subjective Self Rating Test (SSRT) methods. The results showed that the level of mental workload of students was in the high classification with the NASA-TLX dimensions of effort, mental needs, and performance. The level of student fatigue is in the moderate classification with part of the SSRT, namely the weakening of activities. The results of the correlation test show that there is a relationship between mental workload and student fatigue levels with a positive direction of relationship.